The Values of Local Wisdom on Legenda Batu Porang Ni Aji in Batak Toba - Tidora Putri Sibarani; Halimatussakdiah (Tradition and Modernity of Humanity, 2026)
This study examines the values of local wisdom embodied in the Legenda Batu Porang Ni Aji, a traditional Batak Toba legend originating from Pangunjungan Village, Habinsaran District, Toba Regency, North Sumatra. The legend narrates the tragic consequences of an incestuous relationship between two siblings, which ultimately results in their transformation into stone as divine and customary punishment. Employing a qualitative descriptive approach through folklore analysis, this study explores the moral, cultural, and social values reflected in the narrative based on the concept of local wisdom. The findings reveal that the legend primarily functions as a medium for preserving moral principles and reinforcing the Batak Toba kinship system, particularly the prohibition of incest and the importance of maintaining family honor. The analysis identifies seven major elements of local wisdom, five of which emphasize peace-oriented values, including self-control, politeness, social solidarity, belief in God, and moral education, while two represent prosperity-oriented values, namely diligence and work ethic. The dominance of peace-related values demonstrates that the legend serves as an effective mechanism of social control, cultural preservation, and character education. Consequently, Legenda Batu Porang Ni Aji remains highly relevant in contemporary society as a cultural instrument for transmitting ethical values, strengthening collective identity, and preserving the traditional wisdom of the Batak Toba community amid ongoing social and cultural transformation.